Exploring Madrasah Principal Leadership Management in Enhancing Teacher Performance - Karmila; Sumirah; Boby Yasman Purnama (Al-Qalam Institue, 2026)
This study aims to analyze the leadership management of a madrasah principal in improving teacher performance. A qualitative approach with a descriptive method was employed. Data were collected through observations, in-depth interviews, and documentation involving the madrasah principal and teachers as research participants. The data were analyzed using data reduction, data display, and conclusion drawing techniques, while data validity was ensured through source and technique triangulation. The findings reveal that the principal’s leadership management is implemented through four main managerial functions: planning, organizing, implementation, and supervision. Supporting factors include effective collaboration among school members and strong teacher commitment, whereas inhibiting factors consist of low discipline among some teachers, limited facilities and infrastructure, and insufficient motivation for professional self-development. To address these challenges, the principal applies several strategies, such as strengthening communication, conducting academic supervision and guidance, providing motivation, and involving teachers in decision-making processes. This study implies that effective leadership management plays a crucial role in enhancing teacher performance and can serve as a reference for improving leadership practices in madrasah education.